2023
DOI: 10.3390/biomedicines11010222
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Modulation of Learned and Innate Behaviors in Dopamine Transporter Knockout Rats by Guanfacine

Abstract: Investigation of the precise mechanisms of attention deficit and hyperactivity disorder (ADHD) and other dopamine-associated conditions is crucial for the development of new treatment approaches. In this study, we assessed the effects of repeated and acute administration of α2A-adrenoceptor agonist guanfacine on innate and learned forms of behavior of dopamine transporter knockout (DAT-KO) rats to evaluate the possible noradrenergic modulation of behavioral deficits. DAT-KO and wild type rats were trained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…The presented software for CED interface offers an affordable and straightforward approach for performing experiments on PPI of acoustic startle response. Similar to earlier articles [ 9 , 10 ], this study showed high effectiveness and valid output results.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The presented software for CED interface offers an affordable and straightforward approach for performing experiments on PPI of acoustic startle response. Similar to earlier articles [ 9 , 10 ], this study showed high effectiveness and valid output results.…”
Section: Discussionsupporting
confidence: 86%
“…According to the results of experiments in mice (males and females), DAT-KO animals demonstrated a reduced prepulse inhibition compared to WT mice [ 8 , 17 ]. According to the results of our previous experiments in male DAT knockout rats [ 9 , 10 ], ASR in response to single pulses was generally higher than to prepulse+pulse pairs, and PPI in male DAT-KO rats was significantly lower than in male WT rats. The data obtained in female WT and DAT-KO rats show the same tendency; ASR to single pulses is higher than ASR to prepulse+pulse pairs, and PPI in female DAT-KO rats is reduced compared to that in female WT.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, the neural and molecular mechanisms that underlie these cognitive functions are not fully elucidated. For decades, researchers have been fascinated by the neurobiological and molecular basis of acquiring, storing, and retrieving information [ 1 ]. Recent neuroimaging technologies have provided valuable insights into underlying neuroanatomical brain circuits [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%